Implementasi Pendidikan Akhlak dalam Membentuk Karakter Menghormati Guru dan Orang tua di Kelas IV SD Negeri 056627 Kwala Sawit - Tika Sri Handayani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study investigates the implementation of moral education in shaping students' character to respect teachers and parents at SD Negeri 056627 Kwala Sawit. The background highlights the need for integrating moral values into education to foster good character among students. The research aims to evaluate the effectiveness of various teaching methods and the involvement of parents in reinforcing these values. A qualitative approach was employed, utilizing direct observations, interviews with teachers, students, and parents, as well as document analysis related to the moral education curriculum. The findings indicate that while there is a significant improvement in students' attitudes towards respecting teachers and parents, challenges such as varying levels of understanding and collaboration between school and home persist. This research underscores the importance of a comprehensive approach in moral education to cultivate a generation with strong ethical foundations.